Penerapan Pidana Mati di Indonesia dalam Literatur Hukum dan Hak Asasi Manusia - Bima Guntara; Fikri Jamal (Program Studi Hukum Universitas Pamulang, 2021)
Sentencing is an important part of the criminal justice process. The implementation of the death penalty by the state through a court decision means that the state takes the convict's right to life which is a human right that cannot be reduced under any circumstances (non-derogable rights). Therefore, its implementation must pay attention to the human rights of the convict. The purpose of this study is to find out how the death penalty is applied in Indonesia and how to analyze the death penalty in Indonesia in the legal and human rights literature. The research method in this study includes library research, the main method that the author uses in collecting data is documentation. While the primary data is in the form of sources of Indonesian Criminal Law in the form of the Criminal Code and in particular some documentation on human rights and legislation outside the Criminal Code applicable in Indonesia. The secondary data are materials or references obtained from books, articles, journals and from the internet that are relevant to this problem. The regulation of the death penalty in Indonesia is contained in the Criminal Code legislation and outside the Criminal Code. According to statistical data and the hypotheses of several criminologists, the practice of capital punishment in Indonesia has not been proven to provide a deterrent effect to reduce crime rates. In addition to not providing a deterrent effect, the death penalty also violates the convict's right to life. The right to life is guaranteed in several human rights instruments, as stated in several articles of the Universal Declaration of Human Rights, International Covenant on Civil and Political Rights, American Convention on Human Rights, Law no. 39 of 1999 on Human Rights, and the Charter of Fundamental Rights of the European Union. In fact, the right to life is also guaranteed in Indonesia's highest constitution, namely Article 28I of the 1945 Constitution Keywords: Death Penalty, Law and Human Rights